HBR Guide to Office Politics : Rise Above Rivalry Avoid Power Games - Build Better Relationships - Karen Dillon (Harvard Business Review Press, 2015)
Every organization has its share of political drama: Personalities clash. Agendas compete. Turf wars erupt. But you need to work productively with your colleagues even the challenging ones for the good of your organization and your career. How can you do that without compromising your integrity? By acknowledging that power dynamics and unwritten rules exist--and constructively navigating them. Whether you're a new professional or an experienced one, this guide will teach you how to: Build relationships with difficult people Gain allies and increase your sphere of influence Wrangle resources Move up without alienating your colleagues Avoid power games and petty rivalries and Claim credit when it's due.